2015
DOI: 10.1007/s00420-015-1025-2
|View full text |Cite
|
Sign up to set email alerts
|

Disease-generic factors of work participation of workers with a chronic disease: a systematic review

Abstract: PurposeThe purpose of this review was to search systematically for disease-generic factors associated with either work retention (WR) or return to work (RTW) in people of working age with a chronic disease.MethodsAn extensive search was performed in PubMed, EMBASE, PsycINFO and CINAHL for English-, Dutch- and German-language studies searching on synonyms of the terms chronic disease, WR and RTW. Studies were selected if they described factors related to WR or RTW and included participants with a chronic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 28 publications
2
47
0
5
Order By: Relevance
“…Various factors influence the process of work participation which is either related to the disease or irrespective of diagnosis. Considering this last category, previous research indicated that work participation is influenced by both personal factors (eg, age, education,31 gender,31 32 prediction of one's own RTW31 33) and work-related factors (eg, heavy manual work,32 perceived control over work situation33). Interventions to enhance work participation should therefore aim to restore the balance between personal abilities and job demands by modifying factors associated with work participation.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors influence the process of work participation which is either related to the disease or irrespective of diagnosis. Considering this last category, previous research indicated that work participation is influenced by both personal factors (eg, age, education,31 gender,31 32 prediction of one's own RTW31 33) and work-related factors (eg, heavy manual work,32 perceived control over work situation33). Interventions to enhance work participation should therefore aim to restore the balance between personal abilities and job demands by modifying factors associated with work participation.…”
Section: Discussionmentioning
confidence: 99%
“…17 Higher educational levels and male gender were associated with more employment. 17 Higher educational levels and male gender were associated with more employment.…”
Section: Predictors For Employment and Limitations At Workmentioning
confidence: 99%
“…7 Higher rates of unemployment, disease-related work absences, and limitations at work have been reported in adults with CHD compared to the general population in The Netherlands, Germany, Denmark, the United Kingdom, and the United States. 17 These findings were associated with older age, female sex, perceived health complaints, and limitations in daily physical activities caused by the disease. [14][15][16] Research in other chronic diseases (eg, rheumatoid arthritis, asthma, chronic obstructive pulmonary disease, diabetes mellitus, and ischemic heart disease) has consistently shown that employment and work ability are negatively influenced by these conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research has revealed that sick leave is determined by many different factors (Dekkers-Sánchez et al 2013; World Health Organization 2001). In addition to disease-related and environmental factors, person-related factors such as cognitions and perceptions of employees also play a role in work participation (Dekkers-Sánchez et al 2013; Iles et al 2008; Vooijs et al 2015). Research by Dekkers-Sánchez et al (2013) has revealed that physicians identify person-related factors as important factors for RTW.…”
Section: Introductionmentioning
confidence: 99%